Exploring mechanical work changes in controlled ankle motion (CAM) boot walking: The effects of gait speed and shoe levelling - Aaron Thomas; David E. Lunn; Josh Walker (PLoS ONE, 2025)
Preferred walking speed (PWS) is lower when wearing a controlled ankle motion (CAM) boot, which can potentially make comparisons between footwear conditions difficult. Standardising walking speed accounts for this but lacks the ecological validity of PWS. The aim of this study was to compare acute biomechanical responses to CAM boot wear when walking is freely chosen and when it is controlled. Twelve healthy participants walked on an instrumented treadmill at their PWS and at three standardised speeds: 3, 4, and 5 km/h. They did so in three footwear conditions: (1) with a Rebound® Air Walker CAM boot on the right leg, (2) with a Rebound® Air Walker on the right leg and an Evenup Shoelift™ on the left, and (3) in normal footwear. Comparisons between footwear conditions were largely similar in the ipsilateral limb at PWS and at the standardised speeds, which included a decrease in total mechanical work and ankle joint work during CAM boot wear (p < 0.001). At the standardised speeds, total mechanical work and hip joint work were lower during CAM boot wear than wearing normal shoes and the Evenup Shoelift™ (p ≤ 0.014), although there were no differences between footwear conditions at PWS (p ≥ 0.095). As such, acute responses to CAM boot wear are different when speed is standardised compared to when speed is freely chosen, meaning conclusions cannot necessarily be transferred between approaches. Based on these differences observed between walking speeds, it would be prudent for future studies to try to maintain ecological validity by using PWS.